The Islamic Legal Framework of Sadd al-Zarī‘ah and Environmental Policy: Evaluating the Permissibility of Sea Sand Exports in Indonesia - Ashfa Azyan Zulfany; Faishal Agil Al Munawar (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2026)
As an archipelagic country rich in marine sand resources, Indonesia faces a critical dilemma between exploiting this potential for economic gain and ensuring the protection of its marine ecosystems. This issue is central to the analysis of Government Regulation No. 26 of 2023 concerning the Management of Sedimentation Products at Sea, which effectively reopens sea sand exports.  This study aims to examine the sea sand export policy regulated in Government Regulation No. 26 of 2023 and evaluate its compatibility with the Islamic legal principle of Sadd al-Zarī’ah, which prioritises the prevention of harm. Using a normative juridical method that combines legislative and conceptual approaches, this study analyses primary, secondary, and tertiary legal materials. The findings indicate that the regulation contradicts the principles of ecological justice and constitutional mandates (Articles 33 and 28H of the 1945 Constitution), lacks a solid delegative legal basis, and was formulated with insufficient public participation. From the perspective of Sadd al-Zarī’ah, this policy falls under the third category of zarī’ah classified by Ibn Qayyim. This is an action that is permissible (mubah) but causes significant harm (mafsadah). Given that all the conditions for applying Sadd al-Zarī’ah are met, Government Regulation No. 26 of 2023 is considered worthy of revocation and requires revision into a policy that is fair, environmentally friendly, sustainable, and in accordance with sharia and constitutional values. This study notes by urging policymakers to design regulations that truly balance economic interests with long-term ecological sustainability, integrate meaningful public participation, and adopt a preventive legal approach to prevent further environmental degradation.